Genotype Distribution of CNDP1 Polymorphisms in the Healthy Chinese Han Population: Association with HbA1c and Fasting Blood Glucose - Shiqi Zhang; Juan Xu; Di Cui; Shujuan Jiang; Xin Xu; Yi Zhang; Dongchun Zhu; Li Xia; Benito Yard; Yonggui Wu; Qiu Zhang (Journal of Diabetes Research)
We have previously reported that the CNDP1 (CTG)5 allele affords protection against diabetic nephropathy (DN) in patients with Type 2 diabetes (T2DM) of Caucasian origin. Because the incidence of ESRD attributable to both Type 1 diabetes (T1DM) and T2DM is higher among South Asian than Caucasian people, the present study assessed relevant CNDP1 polymorphisms and their association with metabolic parameters in the Chinese Han population. To this end, the (CTG)n allele distribution along with 5 relevant SNPs in the CNDP1 gene, previously reported to be associated with DN in non (CTG)5 carriers of Afro-American ethnicity, were determined in 663 healthy individuals. The (CTG)6 homozygous genotype was the most prevalent (84.5%) genotype in the Chinese Han population. The (CTG)5 and (CTG)4 alleles were present in a small minority of individuals accounting for 15.2% and 0.3% of genotypes with at least one (CTG)5 or one (CTG)4 allele, respectively. Only 0.5% of individuals carried the homozygous (CTG)5 genotype and individuals carrying the homozygous (CTG)4 genotype were not found. The minor allele frequencies (MAFs) of the 5 SNP were 0.197 (C allele for rs4892247), 0.0855 (C allele for rs62099905), 0.085 (G allele for rs62099906), 0.066 (T allele for rs62099907), and 0.18 (A allele for rs72979715). All the SNPs except rs4892247 genotypes were in the Hardy-Weinberg equilibrium. Neither the (CTG)n polymorphism nor the latter three SNPs reached significance when compared with different metabolic parameters. In contrast, individuals with the TT genotype of rs62099905 presented lower fasting blood glucose but higher HbA1c levels. In conclusion, the rs62099905 in the CNDP1 gene is associated with serum glucose levels in the healthy Chinese Han population, while for the CNDP1 (CTG)n polymorphism, no association with serological parameters was found.